CONE-BEAM CT ANALYSIS OF UPPER AIRWAY AND MANDIBLE IN CHILDREN WITH OBSTRUCTIVE SLEEP-APNEA - Daniel Marciuc; Emilia Adriana Marciuc; Bogdan Ionut Dobrovat; Roxana Mihaela Popescu; Bianca Codrina Morarasu; Stefan Morarasu; Valentin Munteanu; Vasilica Toma; Danisia Haba (Romanian Journal of Oral Rehabilitation, 2023)
Obstructive sleep apnea syndrome (OSAS) is a relatively common condition and the cause of neurocognitive and cardiovascular morbidity in children. The aim of this study was to demonstrate if there is a correlation between upper airway volume and area and mandibular dimensions and the presence of OSA in children. We retrospectively analyzed 82 patients (43 diagnosed with OSA and 29 healthy ones) using CBCT images and calculated the upper airway volume and area and 3 mandibular parameters. There were statistically significant differences between group 0 (control) and group 1 (OSA patients) with smaller upper airway volume and area and antero-posterior diameter of cross-sectional minimal airway area in OSA patients, but no significant differences regarding the mandibular measurements between the two groups. In conclusion, the impact of pediatric OSA on health and well-being underscores the importance of early identification and appropriate management.